Kedudukan Metode al-Qāfah Dalam Penetapan Nasab Anak Menurut Ulama Perspektif Maqashid al-Syariah - Agustin Hanapi; Imanuddin Imanuddin; Khairuddin Hasballah (Fakultas Syariah, 2022)
Abstract:This study attempts to identify the position of Qāfah method in determining the child's lineage based on the scholars’ perspective using a qualitative approach through descriptive analysis. The results show that the al-qāfahmethod is important in Islam, particularly in certain cases of denial or claims against children. It is because not all people are willing to do a DNA test due to its complicated mechanism and unpreparedness of the parents to admit the child when the DNA test proves positive. Sholars’ views on the position of the al-qāfahmethod in determining the child’ lineage are varied. First, Hanafiyyah scholars absolutely reject this method because it prioritizes the theory of li'an law when the husband denies the lineage of his child. Second, most other scholars (Maliki, Shafi'i, Hambali, Al-Zahiri, and Al-Auza'i) accept the method by referring to Umar’s decision of engaging lineage experts (qā'if) in determining the child claims. Third, the Zahiri school believes that al-qāfah method can be used as a benchmark in determining the case of lineage and atsar (tracing the traces). The last, Ibn Qayyim considers that al-qāfahmethod as one of the laws established by the Prophet Muhammad.Keywords: Al-Qafah; fiqh; child’s lineage.Abstrak:Penelitian ini bertujuan untuk melihat kedudukan metode al-qāfah dalam menetapkan nasab anak menurut ulama dan perspektif maqasid syariah melalui pendekatan kualitatif dengan cara dekriptif-analisis. Data diperoleh dengan cara mencari literatur yang berkaitan dengan pokok permasalahan kemudian dianalisis dengan metode deskriptif analitik, metode komparatif, dan metode analisis konten. Hasil penelitian menunjukkan bahwa beberapa ulama fikih termasuk di antaranya jumhur ulama menyepakati metode al-qāfah sebagai cara untuk menetapkan nasab anak dengan merujuk tindakan Umar yang menghadirkan ahli nasab (qā’if) dalam perkara sengketa klaim anak. Juga mazhab Zahiri yang mengatakan bahwa al-qāfah dapat dijadikan patokan dalam putusan perihal nasab dan atsar (menelusuri jejak), serta Ibnu Qayyim yang meyakini al-qāfah menjadi salah satu di antara hukum yang ditetapkan Rasulullah SAW). Dalam perspektif maqasid syariah metode al-qāfah penting dilakukan terutama pada kasus pengingkaran atau klaim terhadap anak, lantaran tidak semua masyarakat bersedia melakukan tes DNA karena biaya yang mahal, mekanisme yang rumit juga ketidaksiapan untuk mengakui seandainya diketahui bahwa itu adalah anaknya.Kata Kunci: Al-Qafah; fikih; nasab anak.